2020
DOI: 10.3389/fpsyt.2020.00821
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Behavioral Responses to the COVID-19 Pandemic in Greece

Abstract: Objective: Fear of COVID-19 was associated with more severe depressive and anxiety symptoms. This study aimed to explore COVID-19-related fear, depressive and anxiety symptoms, social responsibility, and behavioral responses during the COVID-19 pandemic in Greece. Method: A cross-sectional study was conducted from April 10 to April 13, 2020. Members of the Greek general population completed anonymously an online survey, distributed through the social media. Among the 3,700 adult respondents, 3,029 fulfilled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
163
6
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(206 citation statements)
references
References 60 publications
19
163
6
9
Order By: Relevance
“…Moreover, cutoff points showed significant predictive power for anxiety, health anxiety, and posttraumatic stress symptomatology. The strong relationship between the FCV-19S scale and anxiety has been demonstrated in recent studies (Harper et al 2020;Tsipropoulou et al 2020;Parlapani et al 2020aParlapani et al , 2020b, proving the scale's utility in identifying stressful emotions. Health anxiety symptomatology, an expected consequence of prolonged fear due to a perceived threat to health (Winter et al 2020), was also related to a more severe fear of COVID-19 (Mertens et al 2020).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Moreover, cutoff points showed significant predictive power for anxiety, health anxiety, and posttraumatic stress symptomatology. The strong relationship between the FCV-19S scale and anxiety has been demonstrated in recent studies (Harper et al 2020;Tsipropoulou et al 2020;Parlapani et al 2020aParlapani et al , 2020b, proving the scale's utility in identifying stressful emotions. Health anxiety symptomatology, an expected consequence of prolonged fear due to a perceived threat to health (Winter et al 2020), was also related to a more severe fear of COVID-19 (Mertens et al 2020).…”
Section: Discussionmentioning
confidence: 78%
“…Administration of selfreported questionnaires instead of clinician-administered interviews to address psychiatric symptomatology may have resulted in response bias. Lastly, women were overrepresented, roughly comprising four-fifths of the sample, something that may have influenced study results, since women were shown to display significantly higher levels of COVID-19-related fear compared with men (Parlapani et al 2020b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences may indicate that older adults have a greater awareness of the risks of COVID-19 than younger adults. These differences may also indicate potential misperceptions of COVID-19 risk among younger populations [ 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%